2013 12th International Conference on Optical Communications and Networks (ICOCN) 2013
DOI: 10.1109/icocn.2013.6617226
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-wideband microwave-photonic chaotic radar for remote ranging

Abstract: A UWB microwave-photonic chaotic radar system for remote ranging is proposed and demonstrated. The chaotic detection signal is transmitted by an ultra-wideband transmitting antenna after a 24 km single-mode fiber transmission to a remote antenna unit. The received signal is converted into the corresponding optical signal through directly modulating and carried by another approximately 24 km single mode fiber back to the central station. The target detection and ranging are accomplished through cross correlatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Through 10-km optical fiber distribution, and within 3-m spatial distance, the range resolutions of 10 cm using EDFA-ASE and of 20 cm utilizing SBS-ASE were obtained respectively. In our preliminary experiments, we proposed a UWB microwave-photonic chaotic radar for remote ranging [30] and for remote water-level monitoring [31]. In 2014, Zheng et al demonstrated a fiber-distributed UWB noise radar, which has a space resolution with cm-level after 3-km fiber transmission [32].…”
Section: Introductionmentioning
confidence: 99%
“…Through 10-km optical fiber distribution, and within 3-m spatial distance, the range resolutions of 10 cm using EDFA-ASE and of 20 cm utilizing SBS-ASE were obtained respectively. In our preliminary experiments, we proposed a UWB microwave-photonic chaotic radar for remote ranging [30] and for remote water-level monitoring [31]. In 2014, Zheng et al demonstrated a fiber-distributed UWB noise radar, which has a space resolution with cm-level after 3-km fiber transmission [32].…”
Section: Introductionmentioning
confidence: 99%